Selected theories of the firm as a base for negotiation description (Economic and Political Thought, 2017)
The article is of a theoretical nature and is based on a comparativeanalysis of the literature on the subject. Its aim is to present the syntheticcharacteristics of those of firm theories (economic ones and managementconcepts related to them) which are most important for the description ofnegotiation processes in a company, as well as to show for what purposesthese theories can be used in the area under consideration. Undertakingthe above-mentioned objectives is justified by the need, on the one hand,to create theoretical foundations of the precise and comprehensiveidentification and analysis of negotiation processes in the enterprise and, onthe other hand, to provide the necessary conditions for the efficient executionof these processes, i.e. their planning, conducting and summing up. In thesubsequent part of the paper the following theories are characterised: ofinter-organisational relationships, transactional costs, stakeholders, contractand agency. The presentation of each of them comprises two components:its synthetic characteristics and determining its place and role in conductingnegotiation processes in a company. In the summing up section of the paperthe conclusions from the considerations are presented as well as the directionsof further studies are indicated.